The personalization of smartphone use by mothers from low-class family in Palembang - Meilinda, Nurly; Sarwono, Billy K; Salamah, Ummi (Universitas Bunda Mulia, 2024)
The societal impact of technological advancements is profound, leading to significant transformations in the way people live. However, a significant proportion of the population continue to be marginalized and excluded. This study aims to examine the complex dynamics that shape the adoption and integration of technology into the daily lives of mothers from low class families. It also investigates how these mothers overcome challenges and leverage the opportunities presented by smartphones to benefit their lives. This study employs a constructivist paradigm and utilizes phenomenological approaches using social construction of technology framework. The data collection was done through in-depth interviews with 10 mothers in Palembang City who met the specified requirements for informants. This study shows that the social and economic factors are the primary factors behind technology appropriation process of mothers from low-class families. They strategically manage their use of mobile technology to meet the unique and particular demands of each home. The results of this study demonstrate that technology is not merely a functional instrument; it is also an entity that is embedded with social and cultural significance, making it inextricably linked to the social dynamics and gender context.